Design of a 0.6 kWp photovoltaic central for a house located in chone canton ecuador - Rodríguez, Jesús Alberto Pérez; Borges, Ciaddys Gina Rodríguez; Quiroz, Carlos Alejandro Bowen; Bailón, David Alejandro Anchundia (International research journal of management, IT and social sciences, 2020)
Grid-connected renewable energy systems are one of the most widely used applications in recent years, due to their great potential in semi-urban areas close to the electricity grid. An electric demand study was carried out in a house located in the Chone canton, province of Manabí, Ecuador, to determine the nominal power for the dimensioning of the system. Chone canton has a great potential for a photovoltaic generation thanks to the high levels of solar radiation it receives. The software PVsyst v. 6.70 was used to design the photovoltaic system, together with other parameters such as energy demand and consumption patterns over time. The analysis revealed a nominal power of 0.6 kWp that would satisfy the diurnal consumption of the dwelling. In addition, the implementation of this system would avoid the emission of 0.81 tons of CO2 per year.